Les erreurs lexicales des étudiants chinois spécialistes de français en 2e année de licence en expression écrite - Julie Bohec (Recherches en didactique des langues et des cultures)
We observed gaps concerning the vocabulary use in writing papers for Chinese students in second year of bachelor degree whose major is French. Those mistakes risk to become fossilized during the third and fourth year if we do not manage to find a solution for it. So, the objective of this research, based on Fahandej Saadi’s research (2010), is to reduce the vocabulary mistakes in the papers. In this research, we wondered how we can help students in this field and we assigned an activity different from their learning habits about the points posing more problems (some words use, repetitions, anglicisms) then, we gave them a questionnaire to know their point of view about this subject and about an approach that they are not used to in China, country where grammar-translation method is still employed in some classes and where mistakes are badly tolerated.